Principles for evaluating health risks from chemicals during infancy and early childhood : the need for a special approach (Geneva, 1986)
"Elaborates basic principles for the evaluation of chemical toxicology that are specific to the physiological characteristics of infants and young children. Principles of evaluation, which were worked out by 46 leading experts, are based on a thorough review of data on postnatal physiology, metabolism, and the special factors governing exposure in this age group, including behavioural and cultural conditions. The report opens with background information on relevant features of postnatal morphology, biochemistry, and physiology. Subsequent chapters assess the kinetics of absorption, biotrans-formation, and elimination, and point out ways in which certain conditions of postnatal development will influence the effects of chemicals on different organs and systems. The book concludes with a discussion of factors that can assist in the identification of children at risk. "